TI_GERICHTE 12.2017.93 vom 27. November 2018 , Banca - contratto di consiglio agli investimenti - responsabilità - valuta - TI Tribunale d'appello (2018)
Banca - contratto di consiglio agli investimenti - responsabilità - valuta